Answer:
3x³ + x² - 2
Step-by-step explanation:
a) 3(x squared plus 3x cubed - 2)
x squared = x²
3x cubed = 3x³
3(x squared plus 3x cubed - 2)
= 3(x² + 3x³ - 2)
= 3x² + 9x³ - 6
Rearrange according to power
= 9x³ + 3x² - 6
When the expression is divided by 3, it is equivalent to
3x³ + x² - 2
Answer:
"no more than 5"
"less than or equal to 5"
.
I can't see your inequalities or the thing your question called expressions.
Step-by-step explanation:
If is no more than it is less than or equal to.
So no more than 5 means less than or equal to 5.
.
Answer:
Step-by-step explanation:
x-intercept: Set y = 0 and solve for x:
0 = mx + b, or mx = -b, or x = -b/m. x-intercept is then (-b/m, 0)
y-intercept: Set x = 0 and solve for y: y = m(0) + b, or y = b. y-intercept is then
(0, b).
Answer:
1) 60
2) 60
3) 119
4) 59
Step-by-step explanation:
All triangle angles add up to 180 degrees. All lines with transversals add to 180 degrees. Use these rules and the measurements given to solve.